2011
DOI: 10.1073/pnas.1111314108
|View full text |Cite
|
Sign up to set email alerts
|

The conserved GTPase Gem1 regulates endoplasmic reticulum–mitochondria connections

Abstract: Mitochondria are connected to the endoplasmic reticulum (ER) through specialized protein complexes. We recently identified the ER-mitochondria encounter structure (ERMES) tethering complex, which plays a role in phospholipid exchange between the two organelles. ERMES also has been implicated in the coordination of mitochondrial protein import, mitochondrial DNA replication, and mitochondrial dynamics, suggesting that these interorganelle contact sites play central regulatory roles in coordinating various aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
321
4
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(351 citation statements)
references
References 32 publications
24
321
4
2
Order By: Relevance
“…Consistent with a role for ERMES proteins in maintaining ER-mitochondrial contacts, phospholipids exchange between the ER and mitochondria was found to slow in cells missing any one of the ERMES proteins (Kornmann et al, 2009). A role for the ERMES complex in mitochondrial lipid homeostasis is also suggested by the genetic interaction of genes encoding ERMES proteins and those required for cardiolipin (CL) biosynthesis (Kornmann et al, 2011), which occurs in mitochondria. However, the role of ERMES in lipid exchange between the ER and mitochondria remains unclear; a recent study found little or no decrease in the transfer of phosphatidylserine (PS) in cells missing ERMES proteins (Nguyen et al, 2012).…”
Section: Introductionmentioning
confidence: 67%
“…Consistent with a role for ERMES proteins in maintaining ER-mitochondrial contacts, phospholipids exchange between the ER and mitochondria was found to slow in cells missing any one of the ERMES proteins (Kornmann et al, 2009). A role for the ERMES complex in mitochondrial lipid homeostasis is also suggested by the genetic interaction of genes encoding ERMES proteins and those required for cardiolipin (CL) biosynthesis (Kornmann et al, 2011), which occurs in mitochondria. However, the role of ERMES in lipid exchange between the ER and mitochondria remains unclear; a recent study found little or no decrease in the transfer of phosphatidylserine (PS) in cells missing ERMES proteins (Nguyen et al, 2012).…”
Section: Introductionmentioning
confidence: 67%
“…Mammalian MAMs are formed by protein tethers, similar to the tetrameric tethering complexes in fungi known as ER-mitochondria encounter structures (ERMES) (Kornmann et al, 2009). However, of the more than 30 proteins involved in vertebrate MAM function, only two of them, GRAMD1A, which corresponds to yeast Lam6p, and MIRO (also known as RHOT1), which corresponds to yeast Gem1p, are conserved in ERMES (Kornmann et al, 2011;Elbaz-Alon et al, 2015). This increased complexity of animal MAMs suggests they acquired new roles beyond those controlled by ERMES (HerreraCruz and Simmen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying this Ca 2 þ -dependent regulation is unclear [7,8]. The GTPase domains of Miro influence mitochondrial morphology [1,4], and both EF hand and GTPase domains regulate endoplasmic reticulum-mitochondrial connections [9,10]. Miro is also a common substrate of the two Parkinson's disease-related proteins Pink1 kinase and Parkin E3 ubiquitin ligase in a signalling cascade that facilitates mitochondrial degradation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%